Changes in biochemical and sensory parameters in industrial blue-veined cheeses in different packaging. (February 2018) - Duval, P.; Chatelard-Chauvin, C.; Gayard, C.; Rifa, E.; Bouchard, P.; Hulin, S.; Delile, A.; Pollet, B.; Montel, M.C.; Picque, D.
Abstract: The effects of packaging on the biochemical and sensory characteristics of industrial blue-veined cheese (pieces of cheeses pre-packaged in materials of different permeability and whole cheeses traditionally wrapped in aluminium foil) were evaluated over 43 days of storage. In cheese pieces in reduced-O2 packaging, less ammonia production and lower proteolysis were observed. Packaged cheese pieces were distinguished from controls by higher levels of (a) methyl ketones and their corresponding alcohols and acids, (b) methyl acids derived from branched chain amino acids and (c) esters. This may be due to less oxidation. Packaged cheese pieces were also more acid, with more pungency, creaminess and milky odour and less bitterness than the control cheeses. They have high moisture content, owing to the low water vapour permeability of the films. Fourme d'Ambert cheese pieces wrapped in permeable film behaved similarly to the corresponding control throughout storage.